2019
DOI: 10.1177/1357633x19850393
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an Internet-based video cognitive processing therapy intervention for veterans with PTSD: A pilot study

Abstract: Introduction There remain a number of UK military veterans who are not able to access psychological therapies for post-traumatic stress disorder (PTSD). Some of these barriers are practical, including the need to balance work and other life commitments with attendance at residential or outpatient appointments. There is a need to investigate more accessible and flexible methods of delivering psychological therapies to veterans. One such alternative is to use remote-access video technology, often referred to as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…A number of facilitators were identified regarding the virtual delivery of trauma therapies to military members, veterans, and PSP ( Table 2 ). These included (1) the convenience of accessing teletherapy, particularly for clients in rural and remote areas [ 79 , 85 , 87 ], (2) the comfort of participating in therapy from the client’s home [ 57 , 59 , 85 , 87 ] resulting in less stress [ 55 , 58 ] and stigma, [ 86 , 87 ], (3) the efficaciousness of several different evidence-based PTSD treatment modalities delivered using digital health, including PE, CPT, CBT, and BA-TE [ 25 , 53 , 56 , 77 ], and (4) the ability to see a therapist from a central health clinic or the location of their choosing reduced travel time and transportation and missed work costs [ 25 , 55 , 82 ]. Many clients found that participating in teletherapy provided the same opportunities for relationship building with the therapist as in-person treatment [ 52 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of facilitators were identified regarding the virtual delivery of trauma therapies to military members, veterans, and PSP ( Table 2 ). These included (1) the convenience of accessing teletherapy, particularly for clients in rural and remote areas [ 79 , 85 , 87 ], (2) the comfort of participating in therapy from the client’s home [ 57 , 59 , 85 , 87 ] resulting in less stress [ 55 , 58 ] and stigma, [ 86 , 87 ], (3) the efficaciousness of several different evidence-based PTSD treatment modalities delivered using digital health, including PE, CPT, CBT, and BA-TE [ 25 , 53 , 56 , 77 ], and (4) the ability to see a therapist from a central health clinic or the location of their choosing reduced travel time and transportation and missed work costs [ 25 , 55 , 82 ]. Many clients found that participating in teletherapy provided the same opportunities for relationship building with the therapist as in-person treatment [ 52 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…digital health engagement was not rated by clients as inferior to in-person therapy when it came to building a relationship with their clinician [ 81 ]. Interestingly, within the included studies, baseline variables such as age, gender, education level, employment status, and relationship status did not appear to correlate with the effectiveness of the psychotherapeutic intervention or the modality of which it was delivered [ 63 , 82 , 84 ]. Although results regarding adherence to therapy and dropout varied throughout the studies, the modality of therapy delivery (digital health or in-person) did not appear to be a predictor of adherence or dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Whether remote care can provide sustained effects for PTSD is inconclusive. A pre-post comparison of patients receiving care through video (with no modality comparison group), showed large effect size between PTSD symptoms at three-month follow-up [32]. However, another study that compared video and in-person care found that patients and providers disagreed on whether treatments had lasting effects: provider-assessments found continuing reduction in symptoms only for in person groups, but patient-reports on symptom reduction at follow-up were comparable across both video and in person [30].…”
Section: Post-traumatic Stress Disorder (Ptsd)mentioning
confidence: 98%
“…Personally, the ability to provide continued care to my patients, and make a meaningful contribution to their well-being during a time when the world turned upside down, helped me mitigate my own stress and anxiety. Importantly, it's becoming clear to me that most evidence-based treatments for PTSD, depression and anxiety are robust and effective in virtual administration, as has been widely reported in research literature 3,4,5,6,7,8,9 . Yet, I quickly learned one hour of virtual care was not equivalent to an hour of face-to-face care, due to the emotional and cognitive demands.…”
Section: ____________________________________________________________mentioning
confidence: 96%